Behavior of tungsten fiber-reinforced tungsten based on single fiber push-out study. (December 2016) - Jasper, B.; Schoenen, S.; Du, J.; Hoeschen, T.; Koch, F.; Linsmeier, Ch.; Neu, R.; Riesch, J.; Terra, A.; Coenen, J.W.
Abstract: To overcome the intrinsic brittleness of tungsten (W), a tungsten fiber-reinforced tungsten-composite material (Wf /W) is under development. The composite addresses the brittleness of W by extrinsic toughening through the introduction of energy dissipation mechanisms. These mechanisms allow the reduction of stress peaks and thus improve the materials resistance against crack growth. They do not rely on the intrinsinc material properties such as ductility. By utilizing powder metallurgy (PM) one could benefit from available industrialized approaches for composite production and alloying routes. In this contribution the PM method of hot isostatic pressing (HIP) is used to produce Wf /W samples containing W fibers coated with an Er2 O3 interface. Analysis of the matrix material demonstrates a dense tungsten bulk, a deformed fiber and a deformed, but still intact interface layer. Metallographic analysis reveals indentations of powder particles in the interface, forming a complex 3D structure. Special emphasis is placed on push-out tests of single fiber HIP samples, where a load is applied via a small indenter on the fiber, to test the debonding and frictional properties of the Er2 O3 interface region enabling the energy dissipation mechanisms. Together with the obtained experimental results, an axisymmetric finite element model is discussed and compared to existing work. In the HIP Wf /W composites the matrix adhesion is rather large and can dominate the push-out behavior. This is in contrast to the previously tested CVD produced samples.